Overview of ADPKD in Pregnancy - Ruth E. Campbell; Charles L. Edelstein; Michel Chonchol (Kidney International Reports)
Autosomal dominant polycystic kidney disease (ADPKD) is a systemic disorder that often affects patients in their third to fifth decades of life and is characterized by kidney cysts, chronic kidney disease (CKD), hypertension, and hepatic cysts. The development of clinical symptoms often coincides with childbearing years. Consequently, there are several considerations regarding pregnant patients with ADPKD. In this review, we detail the effects and management of ADPKD in the peripartum period and discuss family planning options, including assisted reproductive techniques (ART) and preimplantation genetic testing.